Effect of supplementing germinated sprouts of millets on performance, carcass variables, immune and anti-oxidant responses in commercial broiler chickens - RAO, S V RAMA; RAJU, M V L N; PRAKASH, B; RAJKUMAR, U; REDDY, E P K (The Indian Journal of Animal Sciences, 2018)
Germination of millets (sprouts) increases activity of enzymes in grains and availability of amino acid, vitamins and trace minerals to chicken. These nutrients are required for growth, immunity and anti-oxidant system in biological system. An experiment was conducted to study the effects of feeding sprouts of korra, ragi, bajra and sorghum at 5% of expected feed intake from day one to 42 d of age. Total phenolic content among the millets was higher in sprouts of bajra followed by ragi, korra and sorghum in order (148, 110, 95 and 90 mg GAE/g, respectively). A group without feeding sprouts was kept as control. Maize-soybean meal diets having recommended concentrations of nutrients for starter (1–21 d) and finisher (22–42 d of age) phases were fed to all the groups. Maximum and minimum temperature and humidity during the 6-week experimental period were 32.17 and 25.1°C and 60.8 and 33.4%, respectively. Body weight gain and feed efficiency at 42 d of age, slaughter variables (ready to cook yield, relative weights of liver, breast, abdominal fat) and immune responses (antibody titres against ND vaccine, CMI response to PHA-P) were not affected due to feeding of sprouted grains. Lipid peroxidation and activities of glutathione peroxidase, glutathione reductase and super oxide dismutase were significantly less in broilers fed sprouted millets compared to the control group. Based on the results, it is concluded that oxidative stress could be reduced in broiler chicks reared during summer season in open sided poultry house without affecting performance, carcass variables and immune responses.